Solar Energy Utilization for Arid Zone Development - Mann, H S (Annals of Arid Zone, 2016)
In India we are fortunate enough to be amply endowed with solar energy and this bounty can hopeful1y be utilized for a number of rural applications such as pumping of water, drying of agricultural produce, desalination of water, cooking and lighting. It is very necessary that systematic, integrated, time bound and well coordinated research projects are undertaken right now. It is also important that in this futuristic endeavor, the industries are involved from the very beginning and commercial aspects like utilization, production, marketing etc. are kept in view from the start. A high priority should be assigned to the development of a 5 H.P. solar pump. This pump will find ample application in minor irrigation programmes. The development of .such a pump would help in conserving diesel and petrol as wel1 as electricity generated through other means. The development of a suitable low cost and sturdy family size solar cooker will also go a long way in conserving the rural eco-system by sparing cowdung, litter biomass and afforested areas.